Functional Contrast-Enhanced CT for Evaluation of Acute Ischemic Stroke Does Not Increase the Risk of Contrast-Induced Nephropathy - Lima, F.O.; Lev, M.H.; Levy, R.A.; Silva, G.S.; Ebril, M.; de Camargo, É.C.; Pomerantz, S.; Singhal, A.B.; Greer, D.M.; Ay, H.; González, R. Gilberto; Koroshetz, W.J.; et al. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Concerns have recently grown regarding the safety of iodinated contrast agents used for CTA and CTP imaging. We tested whether the incidence of AN, defined by a ≥25% increase in the post−contrast scan creatinine level, was higher among patients with ischemic stroke who underwent a functional contrast-enhanced CT protocol compared with those who had no iodinated contrast administration. MATERIALS AND METHODS: The contrast-exposed group consisted of 575 patients with acute ischemic stroke who underwent CTA (n = 313), CTA/CTP (n = 224), or CTA/CTP followed by conventional angiography (n = 38) within 24 hours of stroke onset and were consecutively enrolled in a prospective cohort study. The nonexposed group consisted of 343 patients with ischemic stroke, consecutively admitted to the same institution, who did not receive iodinated contrast material. Patients were stratified by baseline eGFR. In the primary analysis, the Fisher exact test was used to compare the incidence of AN between the contrast-exposed and the nonexposed patients at 24, 48, and 72 hours and on a cumulative basis. A secondary analysis compared the incidence of AN in patients who underwent conventional angiography following CTA/CTP versus patients who underwent CTA/CTP only. RESULTS: The incidence of AN was 5% in the exposed and 10% in the nonexposed group (P = .003). Patients who underwent conventional angiography after contrast CT were at no greater risk of AN than patients who underwent CTA/CTP alone (26 patients, 5%; and 2 patients, 5%, respectively; P = .7). CONCLUSIONS: Administration of a contrast-enhanced CT protocol involving CTA/CTP and conventional angiography in selected patients does not appear to increase the incidence of CIN. ANacute nephropathyCINcontrast-induced nephropathyCrcreatinineCTACT angiographyCTPCT perfusioneGFRestimated glomerular filtration rateIQRinterquartile rangekV(p)kilovolt (peak)NIHNational Institutes of HealthSTOPScreening Technology and Outcomes Project in Stroke